Determinants of Modern Contraceptive Utilization among Women of Reproductive Age in Cambodia (Medico Legal Update, 2021)
Background: Contraceptive uptake remains a public health concern in Cambodia. Therefore, the aim ofthis study was to determine the modern contraceptive use pattern and itsassociated factors among women ofreproductive age in Cambodia.Method: A cross-sectional study used the data from the Cambodia Demographic and Health Survey. Thissurvey adopted a two-stage stratified random sampling process to select respondents to respond a structuredquestionnaire interview. The multiple logistic regression was applied to determine the association.Results: Of the total 7,606 women, 51.04% used modern contraceptives.Themultivariable analysis indicatedthe use of modern contraceptives was strongly associated with fertility preferences, ideal number of children,number of living children, husband’s desire for children,age at first marriage, number of induced abortions,and marriage to a first birth interval. Health service factors including sources of family planning information,visited health facilities, inaccessibility to health service as well as sociodemographic factors such as women’sage, occupation, and geographical regions also significantly associated with modern contraceptive use.Conclusions: About half of women in Cambodia used modern contraceptives. Reproductive, health serviceand sociodemographic factorswere essential for modern contraceptive utilization.